TRAUMA-INFORMED SOCIAL WORK: A BIBLIOMETRIC EXPLORATION OF RESEARCH TRENDS AND DEVELOPMENTS IN FORENSIC SOCIAL WORK - Dana RAD; Remus RUNCAN; Csaba KISS (International Journal of Social and Educational Innovation)
Integrating ideas of safety, trust, cooperation, and empowerment across many practice areas, trauma-informed interventions have become a necessary paradigm in social work.  Research trends, thematic clusters, and citation impact are examined in this bibliometric analysis of 227 records taken from the Web of Science Core Collection under the terms "trauma-informed strategies" AND "social work".  Trauma and adverse childhood events, trauma-informed care and psychological interventions, post-traumatic stress disorder and mental health, and gender, social determinants, and public health were four thematic clusters found by a co-occurrence analysis of 2568 keywords using VOSviewer reflecting main research directions.  The study emphasizes the changing trauma-informed social work practices, the field's multidisciplinary character, and the growing focus on evidence-based interventions.  Results highlight the need of including trauma-informed ideas into frontline social work practice, policy formation, and educational process.  This study provides insights for practitioners, researchers, and legislators trying to improve trauma-sensitive interventions, so helping to deepen knowledge of trauma-informed research paths.